A comparative analysis of Roman-Persian political and economic periods with contemporary in Islamic perspective - Raid Azhar Romadhan; Achmad Zakaria; Muhammad Rifki; Mashudi; Majdy Kasheem (Islamic Economics Study Program, Faculty of Sharia and Islamic Economics, Universitas Annuqayah, 2024)
This study aims to compare the political economy of the Roman-Persian period and the contemporary era through an Islamic perspective, especially in terms of resource management, wealth distribution, and the influence of policies on society, such as social inequality, resource exploitation, and moral crisis. The research method used is a literature study with a qualitative approach using literature studies on secondary sources. The results showed that the Roman-Persian economic and political system, although effective in maintaining imperial stability, tended to create social inequality due to high taxes and territorial exploitation. Meanwhile, the contemporary economic system presents technological innovation and global economic integration, but it is vulnerable to economic crises and injustices. The conclusion of this study is that Islamic principles such as zakat, the prohibition of usury, and the fair distribution of wealth can be an alternative solution to build a just and sustainable economic system, both in the past and in the present.